2013
DOI: 10.1590/s1413-78522013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Distúrbios de coagulação em pacientes com osteonecrose da cabeça femoral

Abstract: OBJECTIVE: To compare the occurrence of thrombophilic disorders in patients with idiopathic osteonecrosis of the femoral head and patients with secondary osteonecrosis of the femoral head. METHODS: Twenty-four consecutive patients were enrolled, with eight of them presenting idiopathic osteonecrosis and 16 presenting secondary osteonecrosis. The tests for detection of thrombophilic disorders were measurements of protein C, protein S and antithrombin levels and detection of prothrombin and factor V gene mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…h Neck-shaft angle. The canal flare index defined by Noble et al [ 4 ] was D/G. (I) Acetabular abduction angle.…”
Section: Methodsmentioning
confidence: 99%
“…h Neck-shaft angle. The canal flare index defined by Noble et al [ 4 ] was D/G. (I) Acetabular abduction angle.…”
Section: Methodsmentioning
confidence: 99%
“…Protein S deficiency was present in 5.9% of cases with primary ONFH and in 11.8% of cases with secondary ONFH [73]. Similar, Garcia et al found that patients with idiopathic ONFH were 5 times more likely to have protein S deficiency and 2.14 times more likely to have protein C deficiency than patients with secondary ONFH [63].…”
Section: Protein C and Protein S Deficiency And Resistance To Activated Protein Cmentioning
confidence: 72%
“…It is of note that, in their study, all hypercoagulability markers had low prevalence. The study of Garcia et al enrolled 24 Brazilian patients with ONFH and identified zero cases with ATIII deficiency [63]. Very recent published data by Rathod et al [59] showed a lower prevalence of ATIII deficiency in idiopathic ONFH patients compared to healthy controls (11% vs. 22%), suggesting that, when familial thrombophilia is considered a substrate of primary ONFH, the involvement of ATIII deficiency is unlikely.…”
Section: Antithrombin III Deficiencymentioning
confidence: 99%
“…There are indications that osteonecrosis can be induced by decreased blood supply, increased marrow pressure, abnormal coagulation, or toxic effects on bone cells. Many nontraumatic conditions are associated with osteonecrosis [1, 7–9], including corticosteroid use [1012], alcohol overuse [4, 13, 14], hemoglobinopathies [1517], systemic lupus erythematous [18, 19], and coagulation abnormalities [2022].…”
Section: Introductionmentioning
confidence: 99%